Proximal cervical agenesis-laparoscopic reconstruction done in a 13-year-old girl - Kavitha Yogini Duraisamy,; Quraishi, Azhar Un Nisa; Vishnupriya G., (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical agenesis occurs in 1 in 80,000 to 100,000 births, and in 50% of cases it coexists with congenital vaginal agenesis. Isolated cervical agenesis is very rare. We report a case of 13-year-old girl with isolated proximal cervical agenesis. Laparoscopic reconstructive surgery was done. Anastomosis was established between uterus and distal cervical bud. Patient had regular cyclical menstruation following surgery.